Static and Dynamic Responses of a Composite Catenary Riser with Internal Gas–Liquid Two-Phase Flow - Chang, Xueping; Mu, Wencheng (Scientific Journal of Technology, 2026)
This study examines the static and vortex-induced vibration (VIV) responses of a composite catenary riser conveying internal gas–liquid two-phase flow under external ocean currents. A static model of the catenary riser incorporating pipe–seabed interaction is formulated based on the principle of minimum potential energy, and the governing equations are discretized and solved using a finite-difference scheme combined with the Newton–Raphson iterative method.  For dynamics, a wake-oscillator model is coupled with the riser equations to predict combined in-line and cross-flow motions, while the internal two-phase flow is described using the Monette–Pettigrew slip model. The coupled system is solved with a finite-element formulation using Newmark–β time integration and a fourth-order Runge–Kutta scheme. Parametric studies quantify the effects of gas volume fraction and fiber orientation angle on the equilibrium configuration, internal forces, and vibration responses. Results show that increasing gas volume fraction reduces peak tension and bending moment in the touchdown region, whereas smaller layup angles improve the overall load state. In addition, higher gas volume fraction increases vibration amplitudes and shifts the response toward lower-order modes, while larger layup angles primarily induce downstream migration of the dominant mode.